1977
DOI: 10.1111/j.1468-2958.1977.tb00521.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Pragmatic Rules: Devious Messages

Abstract: Consideration of the relationship between semantics and pragmatics leads to a formal analysis of pragmatic implications customarily made by auditors in this culture. The analysis isolates four types of responses to yes‐no demand questions: (1) explication, (2) prepositional implication, (3) relational implication, and (4) transparent question. It further shows how the latter three types can be exploited by devious communicators and proposes some possible social extensions of the system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…It was measured by asking participants the extent to which the distributor was bluffing (measured on a 6-point Likert scale that ranged from 1 = "Not much" to 6 = "Very much") and, then reverse scoring this item. Measuring credibility by ascertaining the extent of bluffing is consistent with both the theory on threats (Ellsberg 1975;Lewicki 1983;Schelling 1960) and the empirical research (Bowers, Elliot, and Desmond 1977;Shapiro and Bies 1994).…”
Section: Perceived Credibilitymentioning
confidence: 90%
“…It was measured by asking participants the extent to which the distributor was bluffing (measured on a 6-point Likert scale that ranged from 1 = "Not much" to 6 = "Very much") and, then reverse scoring this item. Measuring credibility by ascertaining the extent of bluffing is consistent with both the theory on threats (Ellsberg 1975;Lewicki 1983;Schelling 1960) and the empirical research (Bowers, Elliot, and Desmond 1977;Shapiro and Bies 1994).…”
Section: Perceived Credibilitymentioning
confidence: 90%
“…IMT assumes that listeners faced with such messages form general and vague inferences, such as "my partner is being cooperative" and "my partner has disclosed what is relevant." As Bowers et al (1977) argued, listeners respect "respondents' rights to invoke some slippage between the semantic and pragmatic realms, for we recognize the apparent indeterminancy of life and the cultural resistance to dogmatic, absolutist positions" (p. 238). Jacobs et al argue that recipients of covert violations form specific, erroneous implicatures (e.g., "my partner is not currently involved in a casual sexual relationship with someone else").…”
Section: Deceptive Message Processingmentioning
confidence: 96%
“…His primary justification for accepting the CP appears to be that Grice said the CP existed and contained the four maxims. Bowers, Elliot, and Desmond (1977) observed that deviations from these four maxims could conceivably create "devious" messages; Metts (1989) concurred. This is hardly a compelling, logical rationale for accepting the CP as the single unifying construct in information management.…”
Section: Domain Of Conversational Expectationsmentioning
confidence: 87%